1998
DOI: 10.1016/s1097-2765(00)80116-1
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Protein Topology by trans-Acting Factors at the Endoplasmic Reticulum

Abstract: In mammalian cells, the Sec61 complex and translocating chain-associated membrane protein (TRAM) are necessary and sufficient to direct the biogenesis, in the appropriate topology, of all secretory and membrane proteins examined thus far. We demonstrate here that the proper translocation of the prion protein (PrP), a substrate that can be synthesized in more than one topologic form, requires additional factors. In the absence of these additional factors, PrP is synthesized exclusively in the transmembrane topo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
97
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 20 publications
2
97
0
1
Order By: Relevance
“…2B (lanes 2, 5, and 8) shows that these mutations had no effect on PrP topology. As in the WT molecule, PrP containing either G20W or C22Y substitutions produced primarily Sec PrP, with ϳ10% being synthesized as Ctm PrP (Table I, lines [13][14][15]. This result was verified by assaying the topology of these mutants in transfected cells (data not shown).…”
Section: Lack Of Signal Peptide Cleavage Does Not Cause Production Ofmentioning
confidence: 72%
See 1 more Smart Citation
“…2B (lanes 2, 5, and 8) shows that these mutations had no effect on PrP topology. As in the WT molecule, PrP containing either G20W or C22Y substitutions produced primarily Sec PrP, with ϳ10% being synthesized as Ctm PrP (Table I, lines [13][14][15]. This result was verified by assaying the topology of these mutants in transfected cells (data not shown).…”
Section: Lack Of Signal Peptide Cleavage Does Not Cause Production Ofmentioning
confidence: 72%
“…The combined action of both domains operating during the transloca-tion process serves to regulate the proportions of the three topological variants of PrP. Regulatory factors associated with the translocon, in addition to sequence determinants within the PrP molecule itself, have also been shown to influence the final topology achieved (14,15).…”
mentioning
confidence: 99%
“…Intriguingly, the translocation of the prion protein that likewise has multiple folded states related to distinct functions with one particular form being responsible for neurodegeneration has been shown to be also a subject to regulation by as yet unidentified trans-acting cellular factors at the ER (4,5). Similarly, the topological variability of the P-glycoprotein, responsible for multidrug resistance observed in cancer cells, seems to be cotranslationally controlled by ribosomes (1,36).…”
Section: Discussionmentioning
confidence: 99%
“…However, certain proteins have been found to be expressed in two or more topological isoforms, with the heterogeneity apparently generated at the time of translocation at the endoplasmic reticulum (ER) membrane (1,2). In most of these cases, the topological diversity results in protein multifunctionality, suggesting regulatory mechanisms controlling translocational variations at the ER (3)(4)(5). One example of such a protein is the large L envelope protein of the hepatitis B virus (HBV), a polytopic membrane protein existing in a mixed topology (6)(7)(8).…”
mentioning
confidence: 99%
“…More recently, Hegde et al (1998b) have reported that the human prion protein can exist in several forms, including a secreted species and at least two topologically distinct integral membrane forms. The membrane insertion of PrP into reconstituted membranes requires the Sec61 complex and TRAM, but also requires unidentified ER components termed Translocation Accessory Factor( s) (TrAFs) (Hegde et al, 1998~). The extent to which these TrAFs might be generally involved in membrane protein assembly is currently unknown.…”
Section: Membrane-protein Insertionmentioning
confidence: 99%